1999
DOI: 10.1016/s0378-4274(98)00347-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of α2u-globulin in ochratoxin A induced renal toxicity and tumors in F344 rats

Abstract: The mycotoxin ochratoxin A (OTA) was shown to be a potent kidney carcinogen in rats demonstrating a marked sex difference in the response. Compared to female rats, male rats had a 10-fold higher incidence of kidney carcinomas. The objective of this study was to investigate whether this sex difference in tumor response is due to an exacerbation of effect resulting from the interaction of the male rat specific urinary protein h2u-globulin (h2u) with OTA. Male and female rats were treated by oral gavage with OTA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 31 publications
(39 reference statements)
5
19
1
Order By: Relevance
“…In contrary with Rasonyi et al [28], necrotic cells and cell exfoliations in rat kidney treated with ochratoxin were noticed. No hyaline casts were noticed.…”
Section: Discussioncontrasting
confidence: 71%
“…In contrary with Rasonyi et al [28], necrotic cells and cell exfoliations in rat kidney treated with ochratoxin were noticed. No hyaline casts were noticed.…”
Section: Discussioncontrasting
confidence: 71%
“…Indeed many similarities, including atrophic proximal tubules and fibrotic tissue, have been reported between the later stages of BEN and mycotoxin-induced porcine nephropathy (MPN) (Stoev, 1998). Rásony and co-workers reported a similar OTAinduced loss of proximal tubular cells, accompanied with increased regenerative processes, in rats following oral OTA exposure (Rásonyi et al, 1999).…”
Section: Introductionmentioning
confidence: 76%
“…This accumulation initiates a sequence of events that appears to lead to nephropathy and renal tumor formation (Rodgers and Baetcke, 1993). Even though it has been demonstrated that OTA kidney lesions are different from the α2u-nephropathy in all characteristic points (Rasonyi et al, 1999) and that OTA also causes renal tumors in male mice (Bendele et al, 1985), Mantle and Nagy (2008) suggested that the α2u-globulin could act as a specific OTA carrier that increases proximal tubule exposure to the mycotoxin in male rats. However, this has not been demonstrated experimentally.…”
Section: Distributionmentioning
confidence: 99%